2017
DOI: 10.1109/jtehm.2017.2649491
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Paroxysms in Long-Term, Single-Channel EEG-Monitoring of Patients with Typical Absence Seizures

Abstract: Absence seizures are associated with generalized 2.5–5 Hz spike-wave discharges in the electroencephalogram (EEG). Rarely are patients, parents, or physicians aware of the duration or incidence of seizures. Six patients were monitored with a portable EEG-device over four times 24 h to evaluate how easily outpatients are monitored and how well an automatic seizure detection algorithm can identify the absences. Based on patient-specific modeling, we achieved a sensitivity of 98.4% with only 0.23 false detections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 27 publications
0
58
0
Order By: Relevance
“…[1][2][3] Many factors contribute to this problem, with unrecognized and undocumented seizures being the most important. 8,9 Recently, many new EEG devices have appeared, combining various electrode configurations and data processing methods, [10][11][12][13][14][15] but none of these have been tested in real-life. These clinical problems also concern the patients, 6 and in the context of epilepsy research the problem of wrongful reporting is also well known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Many factors contribute to this problem, with unrecognized and undocumented seizures being the most important. 8,9 Recently, many new EEG devices have appeared, combining various electrode configurations and data processing methods, [10][11][12][13][14][15] but none of these have been tested in real-life. These clinical problems also concern the patients, 6 and in the context of epilepsy research the problem of wrongful reporting is also well known.…”
Section: Introductionmentioning
confidence: 99%
“…An EEG acquisition system usable during everyday life could be the tool currently lacking in the toolbox of epilepsy diagnostics and management. 8,9 Recently, many new EEG devices have appeared, combining various electrode configurations and data processing methods, [10][11][12][13][14][15] but none of these have been tested in real-life. In this study, we present the first real-life data on a subcutaneous EEG device for continuous home monitoring of epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Second, algorithms to detect seizures automatically need to be developed using only that limited amount of EEG channels. Previously, reduced electrode montages have been shown useful for seizure detection and documentation for several epilepsy types . Our proof‐of‐concept study showed that behind‐the‐ear EEG is useful for focal seizure detection .…”
Section: Introductionmentioning
confidence: 70%
“…The performance of six commercial devices exceeded that of daytime (F 1 -score = 0.81) and nighttime (F 1 -score = 0.25) patient reports [10,[14][15][16][17][18][19]. ePatch (ECG) was the highest performing commercial SDD (F 1score = 1.00) [16], SPEAC (sEMG, midline bicep) was the highest performing GTC detection device (F 1 -score = 0.95) [10], and Actiwave (wireless EEG) was the highest performing absence SDD (F 1 -score = 0.92) [15].…”
Section: Commercial Sdd Performancementioning
confidence: 85%
“…The majority of the studies included in Table 1, which shows the performance data from the validation studies of commercial devices, were conducted in an Epilepsy Monitoring Unit (EMU)-setting. One study was conducted in an outpatient setting [15].…”
Section: Commercial Sdd Performancementioning
confidence: 99%